Tetraspanin CD9: A Key Regulator of Cell Adhesion in the Immune System - Reyes, Raquel; Cardeñes, Beatriz; Machado-Pineda, Yesenia; Cabañas, Carlos (Frontiers in Immunology, 2018)
The tetraspanin CD9 is expressed by all the major subsets of leukocytes (B cells, CD4+ T cells, CD8+ T cells, NK cells, granulocytes, monocytes and macrophages, immature and mature DCs) and also at a high level by endothelial cells. As a typical member of the tetraspanin superfamily, a prominent feature of CD9 is its propensity to engage in a multitude of interactions with other tetraspanins as well as with different transmembrane and intracellular proteins within the context of defined membranal domains termed tetraspanin-enriched domains (TEMs). Through these associations, CD9 influences many cellular activities in the different subtypes of leukocytes and in endothelial cells, including intracellular signaling, proliferation, activation, survival, migration, invasion, adhesion and diapedesis. Several excellent reviews have already covered the topic of how tetraspanins, including CD9, regulate these cellular processes in the different cells of the immune system. In this mini-review, however, we will focus particularly on describing and discussing the regulatory effects exerted by CD9 on different adhesion molecules that play pivotal roles in the physiology of leukocytes and endothelial cells, with a particular emphasis in the regulation of adhesion molecules of the integrin and immunoglobulin superfamilies.